The Role of Criminal Law in Handling Cyber Crimes: Challenges and Solutions - Maria Alberta Liza Quintarti; Riadi Asra Rahmad; Zulkarnain S; Budi Handayani; Rica Gusmarani (Universitas Muhammadiyah Palu, 2024)
Cybercrime includes various illegal acts committed via the internet or digital technology. With the rapid development of information technology, criminal law is faced with new challenges in dealing with this crime. Cybercrime is any unlawful act carried out via a computer, network or digital device that can harm individuals or society as a whole. Among the forms of cybercrime are online fraud, identity theft, malware and ransomware, hacking and also cyberbullying. In this crime, criminal law has a vital role in dealing with cybercrime through law enforcement, crime prevention, victim protection, increasing law enforcement capabilities, and international cooperation. Continuous efforts are needed to ensure the law can keep up with technological developments and the changing dynamics of crime. Even though it also faces various challenges, it can take appropriate solution steps, such as strengthening regulations, international cooperation, and increasing awareness, so that it can be more effective in fighting cybercrime and protecting society in general.